Experimental Study on the Dielectric Model of Common Asphalt Pavement Surface Materials Based on the L-R Model - Yanhui Zhong; Yanlong Gao; Bei Zhang; Songtao Li; Hongchuan Cui; Xiaolong Li; Han Zhao (Advances in Civil Engineering)
The establishment of a dielectric model of the asphalt pavement surface material is the premise and key to applying the electromagnetic wave technology to asphalt pavement nondestructive testing. Asphalt pavement can be made of different materials, including various types of asphalt mixtures. Therefore, in order to study and analyze the dielectric properties of different types of asphalt mixtures and establish a dielectric model of the asphalt pavement surface material, this paper studies four types of asphalt mixtures commonly used in the asphalt pavement surface course. Based on the comparative analysis of three classical models, the complex refractive index method (CRIM), Brown, and Looyenga; based on the L-R model, the linear regression analysis was conducted on the test data. The dielectric models which are suitable for the interpretation of four types of asphalt mixtures were established, and the dielectric model database of asphalt pavement surface materials was extended, which provides theoretical and technical support for nondestructive testing of the asphalt pavement.